Dominant shareholders, corporate boards, and corporate value: A cross-country analysis - Dahya, Jay; Dimitrov, Orlin; McConnell, John J. (Journal of Financial Economics, 2008)
We investigate the relation between corporate value and the proportion of the board made up of independent directors in 799 firms with a dominant shareholder across 22 countries. We find a positive relation, especially in countries with weak legal protection for shareholders. The findings suggest that a dominant shareholder, were he so inclined, could offset, at least in part, the documented value discount associated with weak country-level shareholder protection by appointing an ‘independent’ board. The cost to the dominant shareholder of doing so is the loss in perquisites associated with being a dominant shareholder. Thus, not all dominant shareholders choose independent boards.